O estado da arte da inf?ncia e da educa??o infantil do campo: debates hist?ricos, constru??es atuais - Gon?alves, Raphaela Dany Freitas Silveira (2013)
The Childhood Education, which is marked by the struggles of social movements for the children?s rights and guarantee these rights in the Brazilian legislation of the past decade, gains in academic political social visibility, obstructed before. Its importance has been the focus of many national and international researches. However, it is still necessary to discuss, in depth, the various childhood and kindergarten facing different audiences. In this research, childhood education in the rural area population/rural understood as Childhood Education Field, has become the object investigated. So this study intends to investigate and map the scientific productions in childhood education and Childhood Education rural in the decade of 2002-2012, a period that marks politics Childhood Education and rural Education. Therefore, the problem is questioned: After a decade, since the determination of the Operational Guidelines for the Childhood Education (CNE/CEB N? 04/00, February 16, 2000) and Rural Education (CNE/CEB N? 1, April 3, 2002) where is the visibility of children in the rural politics Childhood Education (EIC) in scientific production in the decade of 2002 to 2012? Therefore, we chose as the methodological basis the art state (ENZ E ROMANOWSKI, 2006; FERREIRA, 2002), with the objective is to effect the balance of researches in this area. The sources chosen to find this scientific productions were databases of reference in the rural educational: the National Association of Graduate Studies and Research in Education (ANPEd), Coordination for the Improvement of Higher Education Personnel (CAPES) and Scientific Electronic Library Online (SCIELO). To qualify the debate, this text is organized into six dissertative chapters. The first consists of the introductory discussion of the theme. The second chapter, entitled ?A methodological approach: the state of art" presents the methodological option, the sources and categories of research. The third chapter "Politics of Education area: another paradigm for the Rural Education" situates the debate of Education area based on studies Munarim (2006), Fernandes (2006) and Souza (2008). The fourth chapter, "Childhood Education area: a necessary politics" discusses the political career of the Childhood Education, as well as on the integration of this Education area in the politics education nowdays based on theoretical research of Silva, Pasuch and Silva (2012), as well as national documents such as DOEBEC (2002) and Resolution CNE / CEB n ? 2, 2008. The fifth chapter, "The childhood and Childhood Education area in scientific production: research findings" contained in the data analysis, with the results of the research found. The sixth chapter "Research in EIC and its themes announced in interface analysis" consists of the analysis of the texts surveyed and their themes. Finally, the seventh and final chapter, with the final considerations. As a result of this study, it was found that the area of Childhood Education needs urgently for more research that qualify its discussion.